Analisis dan Perancangan Sistem Informasi Pengelolaan Data Aktivitas Mahasiswa Berbasis Website (Studi Kasus: STMIK Primakara) - Ni Luh Gede Devi Darnita Putri; Ketut Queena Fredlina; I Putu Satwika (Universitas Pendidikan Ganesha, 2021)
STMIK Primakara still has problems in managing student activity data because the active system is considered not running optimally. The purpose of this research is to produce an accurate and structured activity data management. The method used in this research is the prototype method and for data collection by conducting observations and field analysis and interviews. The results of this study are students are able to input the activities that have been followed independently. The student department and the operator in charge only validate the data that has been inputted by the student. This study uses the SDLC (System Development Life Cycle) prototype model. To design the system design using the VueJs framework with the primevue component library version 3.0.0 with the sigma-vue template. With this system design, it is hoped that it will make it easier for the development department to design the system so that it can be implemented immediately to students. Keywords— System Design, Data Management, VueJs, Prototype Model, Student Activity